2011
DOI: 10.1175/2010bams3173.1
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Atmospheric Events Leading to the Summer 2010 Floods in Pakistan

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
186
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(199 citation statements)
references
References 18 publications
6
186
0
Order By: Relevance
“…A possible reason may be that convection is more sensitive to lower tropospheric temperature and moisture perturbations than to upper tropospheric ones [e.g., Kuang, 2010;Tulich and Mapes, 2010;Nie and Kuang, 2012]. Results here are consistent with previous observational and modeling studies which have concluded that orographic lifting is the primary cause of the floods of 2010 and other years in the same region [e.g., Houze et al, 2011;Rasmussen and Houze, 2012]. Martius et al [2013] showed that the upper level PV exerted a significant impact on the orientation and amplitude of the lower level flow that forces orographic lifting.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016mssupporting
confidence: 90%
See 2 more Smart Citations
“…A possible reason may be that convection is more sensitive to lower tropospheric temperature and moisture perturbations than to upper tropospheric ones [e.g., Kuang, 2010;Tulich and Mapes, 2010;Nie and Kuang, 2012]. Results here are consistent with previous observational and modeling studies which have concluded that orographic lifting is the primary cause of the floods of 2010 and other years in the same region [e.g., Houze et al, 2011;Rasmussen and Houze, 2012]. Martius et al [2013] showed that the upper level PV exerted a significant impact on the orientation and amplitude of the lower level flow that forces orographic lifting.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016mssupporting
confidence: 90%
“…This devastating event, affecting about 20 million people and submerging one fifth of Pakistan's land area under water, resulted from a series of extremely heavy rainfall events [e.g., Houze et al, 2011] (also see Figure 1a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep and severe convective events occurring in the vicinity of mountainous regions leading to anomalous rainfall and subsequent flooding, have been the focus of research for a long time due to their often disastrous outcome for human settlements and ecosystems (Maddox et al, 1978;Caracena et al, 1979;Nair et al, 1997;Das et al, 2003Das et al, , 2006Houze et al, 2011;Webster et al, 2011;Rasmussen and Houze, 2012;Rasmussen et al, 2014). Houze et al (2011) identified the occurrence of a synoptic-scale channel of anomalously moist flow towards the mountain barrier in Pakistan (JulyÁ August 2010) to be responsible for the development of very wide precipitating mesoscale convective systems (MCS) producing huge runoff and flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptionally high monsoon rainfall over northern Pakistan during July and August (Houze Jr. et al, 2011;Rajeevan et al, 2011;Webster et al, 2011) No substantial trend in heavy rainfall event frequency in northern Pakistan in past several decades (Wang, S.-Y. et al, 2011;Webster et al, 2011) ( low confi dence)…”
Section: Economic Losses Due To Extreme Weather Eventsmentioning
confidence: 99%